The Influence of Personal Branding, Making TikTok Videos, Product Live Streams on Purchase Decisions on the Tiktok Platform - Rinintha Parameswari; Sugandha Sugandha; Agus Kusnawan; Fidellis Wato Tholok; Suhendar Janamarta (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
This research was conducted with the aim of finding out how personal branding, making Tiktok videos, product live streams affect purchasing decisions on the Tiktok platform. The research method used is a quantitative method in which the following conclusions are obtained: the independent variable (alone) has a positive effect and one variable has a less positive effect on the dependent variable on purchasing decisions on the TikTok platform, where t count personal branding is 5,286 greater than t table 1,966, the value t count making tiktok videos 2,560 greater t table 1,966 and t count live stream products of 1,599 greater than table 1,966. F count = 122,733 probability value = 0.000 then F count > F table 122,733 greater (>) 3.00 probability value 0.000 small (<) 0.05, the conclusions drawn are independent variables and have a positive effect on the dependent variable on purchasing decisions on the platform tiktok. The R2 multiple determination value is 78.7% of the purchase decision on the TikTok platform which is explained by the independent variable factors, and the remaining 100% -78.7% = 21.3% excluding the independent variable factors.